The aerodynamic performance of a platoon of lorries in close-proximity during an overtaking manoeuvre - Marshall, Samuel David; Snape, Karl; Soper, David; Sterling, Mark; Gillmeier, Stefanie (Frontiers in Future Transportation, 2024)
For the first time, this paper examines the aerodynamic forces that arise in a platoon of Heavy Goods Vehicle lorries travelling in close proximity during an overtaking manoeuvre. Through an in-depth programme of wind tunnel experiments it is demonstrated that there is a complex relationship between the drag and side force coefficients, with a possible hysteresis-like behaviour shown. The influence of the overtaken lorry on the overtaking lorry is shown to be key in terms of the aerodynamic-induced forces experienced by the latter. Furthermore, the overtaking lorry is shown to benefit aerodynamically from the overtaken lorry, and this is attributed to the elliptical nature of the Navier-Stokes equations. In addition to examining the forces that arise during overtaking, the variation of the wind-induced forces with respect to yaw on a single lorry is compared to those on a middle lorry in a 3-lorry platoon. The aerodynamic benefits arising from platooning/vehicles travelling in close proximity are again demonstrated, although it is shown that these benefits may only exist over a limited range of yaw angles, raising questions about the real-world application of this approach. This has important implications for platooning in crosswinds and the drag force reduction that is assumed due to platooning.